A systematic review of the predictive factors for the recurrence of acute pancreatitis - Daniela Pacella; Adriano De Simone; Adolfo Pisanu; Gianluca Pellino; Lucio Selvaggi; Valentina Murzi; Eleonora Locci; Giulia Ciabatti; Laura Mastrangelo; Elio Jovine; Matteo Rottoli; Giacomo Calini; et al. (World Journal of Emergency Surgery)
Abstract Purpose Acute Pancreatitis (AP) is a prevalent clinical pancreatic disorder characterized by acute inflammation of the pancreas, frequently associated with biliary or alcoholic events. If not treated with cholecystectomy after the first episode, patients may experience a recurrence of AP, with consequent need for emergency surgery and increased risk of death. Analyzing the risk factors that may contribute to the recurrence of Biliary and Alcoholic Pancreatitis (BAP and AAP), future research can be driven toward new solutions for preventing and treating this pancreatic disease. Methods A systematic review was conducted selecting studies from BiomedCentral, PubMed, Scopus and Web of Science by two independent reviewers. Publications were considered only if written in English in the time interval between January 2000 and June 2024 and investigated the risk factors for the recurrence of BAP and AAP. At the end of the selection, a quality assessment phase was conducted using the PROBAST tool. Results In this systematic review, 8 articles were selected out of 6.945, involving a total sample of 11.271 patients of which 38.77% developed recurrence episodes. 37.5% of the included studies focus on recurrent acute biliary pancreatitis (RBAP), while 62.5% are dedicated to recurrent acute alcoholic pancreatitis (RAAP). The risk factors for the recurrence of AP showed a clear differentiation between the alcoholic and biliary etiology. Most of the considered studies adopted a retrospective design, characterized by a susceptibility to potential methodological biases. However, the trend indicated a more recent increase in prospective studies, together with a greater focus on identifying and understanding the possible risk factors associated with the recurrence of acute pancreatitis (RAP). This result highlighted the progress in the scientific approach toward a more rigorous and systematic assessment of the causes and dynamics that influence the recurrence of the disease. Conclusion Studies highlighted the importance of lifestyle factors, clinical complications, and surgical interventions that can impact the risk of biliary or alcoholic recurrent acute pancreatitis. Increased and systematic adoption of artificial intelligence-based tools could significantly impact future knowledge relating to the risks of recurrence and relative possibilities of prevention.